Family socio-demographic profile of carers of dependent patients cared by a family health unit in the city of São Paulo: DOI:10.15343/0104-7809.201012024 - Cintia Hitomi Yamashita; Fernanda Amendola; Márcia Regina Martins Alvarenga; Maria Amélia de Campos Oliveira (O Mundo da Saúde, 2010)
With the increase of life expectancy, the number of individuals with chronic and degenerative diseases, which may cause incapacity and dependence, is growing. Home care of a relative with functional losses and dependence may affect negatively family dynamics and overloads the one responsible for care. The aim of this study was to describe the socio-demographic profile and the family structure of family carers of dependent patients cared by teams of Family Health from a Basic Health Unit of the city of São Paulo and to characterize the patients they care for. It is a transversal, descriptive, quantitative study whose subjects were 67 non-remunerated dependent patients’ family carers with at least 16 years old that cared at the time for more than two months. An instrument was elaborated for socio-demographic characterization. Results show that most (92.5%) carers were female, with an average age of 54.7 years old, 71.6% reported some kind of health problem and 59.7% said they did not receive instructions from the health teams on care centers. From the 69 dependent patients, 55.1% were male, with an average age of 58.8 years old, predominantly with circulatory diseases (29.7%). Amongst the families, 50.7% did not receive aid when they needed and 71.6% reported a good relationship with the patient. Results corroborate the findings of the literature on the dominant profile of family carers. Knowing their profile may contribute for the adoption of intervention strategies for providing for their health necessities.